Applying Intelligent Management Comprehensive System in Rental Estimation of Russian Rare-earth Deposits of Global Resource Cluster; Procedia Chemistry; Vol. 11 : 1st International Symposium on Inorganic Fluorides: Chemistry and Technology, ISIF 2014, Tomsk, Russia - Bogdanov S. V.; Chorny S. A.; Kerbel B. M.; Zhiganov A. N.; Falkovich Yu. V. Yulia Valerievna (2014, 2014)
Title screen